Endometriosis organoids: prospects and challenges. Issue 1 (July 2022) - Esfandiari, Fereshteh; Mansouri, Nahid; Shahhoseini, Maryam; Heidari Khoei, Heidar; Mikaeeli, Gelareh; Vankelecom, Hugo; Baharvand, Hossein
Abstract: Endometriosis is a sex hormone-dependent, painful disease that affects 10–15% of women worldwide with no definitive cure, and current treatments are not always effective. This limitation is mainly due to gaps in our knowledge about the mechanisms involved in the pathogenesis of endometriosis at the cellular and molecular levels. Hormonal dysregulation appears to be responsible for inflammation, angiogenesis, endometrial non-receptivity, embryo implantation failure and infertility in women with endometriosis. Although correlative evidence about possible causes of hormonal dysregulations exists, the functional mechanisms remain unknown. Reliable research models of endometriosis are needed to investigate the exact mechanisms that underlie hormone disruptions. This Commentary discusses the available in-vivo and in-vitro systems for studying endometriosis. The authors emphasize the recently developed human endometriosis organoids as cutting-edge and innovative research models for endometriosis investigations, discuss their advantages and describe challenges that must be addressed to yield a reliable in-vitro model of human endometriosis. Moreover, it discusses microfluidic technology to address the present challenges for producing advanced endometriosis organoids and how to benefit from CRISPR technology to improve our knowledge about disturbed hormonal function in patients with endometriosis.